2010
DOI: 10.1243/09544119jeim795
|View full text |Cite
|
Sign up to set email alerts
|

Transient Elastohydrodynamic Lubrication Analysis of a Novel Metal-On-Metal Hip Prosthesis with a Non-Spherical Femoral Bearing Surface

Abstract: Effective lubrication performance of metal-on-metal hip implants only requires optimum conformity within the main loaded area, while it is advantageous to increase the clearance in the equatorial region. Such a varying clearance can be achieved by using nonspherical bearing surfaces for either acetabular or femoral components. An elastohydrodynamic lubrication model of a novel metal-on-metal hip prosthesis using a nonspherical femoral bearing surface against a spherical cup was solved under ISO standard specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Compared with the ideal spherical bearing geometry, the nonspherical geometries of bearing surfaces, which may be a result of wear, affect the gap between the cup and head surfaces (clearances) and consequently affect lubrication and wear. The change of bearing geometry during wear resulting in a decreased contact pressure was also observed in the EHL studies of hip implants, such that the peak pressure was reduced and pressure was distributed more evenly on the bearing surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the ideal spherical bearing geometry, the nonspherical geometries of bearing surfaces, which may be a result of wear, affect the gap between the cup and head surfaces (clearances) and consequently affect lubrication and wear. The change of bearing geometry during wear resulting in a decreased contact pressure was also observed in the EHL studies of hip implants, such that the peak pressure was reduced and pressure was distributed more evenly on the bearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have shown that the fluid-filled lubricating gap is at nanometer size-an extremely small gap when compared to typical engineering bearing problems, where the fluid-filled gap is typically in a range of 1-100 mm. 14,15 Compared with the ideal spherical bearing geometry, the nonspherical geometries of bearing surfaces, which may be a result of wear, affect the gap between the cup and head surfaces (clearances) and consequently affect lubrication [16][17][18] and wear. The change of bearing geometry during wear resulting in a decreased contact pressure was also observed in the EHL studies of hip implants, 19 such that the peak pressure was reduced and pressure was distributed more evenly on the bearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Such a conforming 1 geometry reduces the pressure gradient at the inlet, resulting in the reduction in the 2 Poiseuille flow and an increase in the Couette flow. As a result, more lubricant is 3 allowed to flow into the loaded area to improve lubrication [35]. Therefore, a decrease 4 in radial clearance from 100 to 30 µm caused the increase of film thickness (Figures 9 5 b and 11).…”
mentioning
confidence: 99%
“…In order to facilitate the numerical process and improve the stability, the governing equations were non-dimensionalized. A multi-grid method [20,21] was used to solve the Reynolds equation. On each grid level, the finite difference method was used to approximate the Reynolds equation.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
“…The central difference was applied to the left hand side of the equation and the backward difference to the right hand terms. The detailed numerical approach was similar to that of the linear elastic model in the previous publications [20,21].…”
Section: Algorithm Descriptionmentioning
confidence: 99%